Development of a motivation-based tool to facilitate individualized self-management interventions for adolescents with asthma. Issue 7 (July 2022) - Byczkowski, Terri L.; Vockell, Anna-Liisa B.; Krier, David J.; Britto, Maria T.
Abstract: Objective: To develop a questionnaire for segmenting adolescents with asthma into archetypes based on their motivations for individualized self-management interventions. Methods: A prospective observational study using segmentation methodology. First, adolescents created photo diaries followed by in-person semi-structured interviews to develop a pool of candidate items for identifying and describing archetypes. Second, quantitative methods were used to test the pool of items to determine which ones best identified each archetype. Results: Six archetypes based on motivations were identified and described: goal oriented visionaries; mentors and helpers; influencers; discouraged adolescents; dependent adolescents; and shame avoiders. A questionnaire with 63 candidate items was administered to 201 adolescents. Confirmatory factor analysis resulted in a 17-item questionnaire that identified the archetypes. Conclusion: This study is the first step towards applying a segmentation methodology to facilitate the application of interventions during a clinic visit to increase adherence. It has shown that a relatively short questionnaire can be used to identify archetypes based on motivations. Practice Implications: The 17-item questionnaire could provide a framework and direction for healthcare professionals to customize existing adherence interventions, such as motivational interviewing, to different segments of adolescents. It would be especially helpful in primary care settings where time is limited. Highlights: Adherence to medication regimens among adolescents with asthma is poor. Tailored interventions based on underlying motivations may improve adherence. Used segmentation methods, a novel approach, to develop archetypes. Used photo-diaries followed by semi-structured in-person interviews. Developed a clinically feasible questionnaire to determine adolescents' archetypes.